(untitled) (Mustansiria Dental Journal, 2022)
Abstract Aim of the study: This study aimed to review the various types of bite raisers used in daily orthodontic practice, their advantages and disadvantages, the fabricated materials, and the biomechanics for each use. Methods: Searching for different types of bite raisers and their applications, indications, and benefits was carried out using different databases, including PubMed Central, Science Direct, Wiley Online Library, the Cochrane Library, Textbooks, Google Scholar, Research Gate, and hand searching till March 2022. After excluding the duplicate articles, information in these papers is summarized and in forms of types, indications, advantages, disadvantages, and effects. Results and Conclusions: There are many types of bite raisers, of which the fixed one is the most applicable as it does not need the patients’ cooperation, yet the material of choice and the type of malocclusion in the case itself may influence the location, type of the material used, its thickness and the purpose of its use. Orthodontists use the most uncomplicated technique to open the bite allowing easy teeth movement.